(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. Sports organizations exist to perform tasks that can only be executed through cooperative effort, and sports management is responsible for the performance and success of these organizations. The main problem concerning sports organizations and making them implement modern management paradigms is the duality of functions, which divides a sports organization into units increasing the internal competition and reducing the possibilities to create new knowledge. This undoubtedly affects the insufficiently productive functioning of a sports organization under modern conditions of globalization. Organizational intelligence (OI) could be a way to promote innovations, create and share knowledge (McMaster, 1998; Winand, Qualizza, Vos, Zintz, & Scheerder, 2013b). Methods. Two questionnaires were used in this research: first, regarding the evaluation of organizational intelligence level, the second regarding the sports organization’s preparation for innovations. Results. One of the lowest evaluated OI factors was organizational openness and the highest rating was given to group work. Comparing OI internal dimensions score of sports organizations which implemented or not innovations during the last 12 months it became clear that there was a significant difference in the scores for organizational openness in sport organizations which implemented innovations and (M = 4.2747, SD = 0.82337) and for sport organizations which did not implement innovations (M = 3.5874, SD = 0.51288), p = .24 (two-tailed). Conclusion. Sports organizations having more features of intelligent organization more analyse innovation development opportunities in various aspects, but the level of intelligence and innovation ideas development has no relation, except for costs analysis. Sports organization becoming intelligent and developing innovations had advantage only in some phases of innovation development: situation analysis and decision making. Keywords: sport federations, organizational culture, readiness to innovation process.